The microbiota–gut–brain axis and its modulation in the therapy of depression: Comparison of efficacy of conventional drugs and traditional Chinese medicine approaches. (September 2022) - Bi, Chenchen; Guo, Shitian; Hu, Shijia; Chen, Jiaqi; Ye, Mengfei; Liu, Zheng
Abstract: Depression is a common and severe mental disease that places a heavy burden on human society, which can lead to decreased cognitive function, energy loss, insomnia, and even suicide. Although medication plays an important role in improving the symptoms of depression, approximately one third of people with depression do not significantly benefit from medication and experience various adverse reactions. Recently, increasing evidence has shown that gut microbes play an important role in the occurrence and development of depression. There have been illuminating studies previously conducted on the relationship between antidepressant chemicals, traditional Chinese medicine, and the microbiota–gut–brain axis (MGBA). Therefore, in this review, we summarize the role of the MGBA in the occurrence and development of depression, especially the important role of the MGBA in the mechanism of action of antidepressants. Modulation of the MGBA is proposed to enhance the efficacy of antidepressant drugs and reduce their side effects and disease recurrence, so as to provide a new method for the treatment of depression. Graphical Abstract: ga1